Spatial and Monthly Variation in Co, Zn and Cd Concentrations of Surface Water of Shatt Al-Hilla River, Babylon, Iraq - J. Baqir1, Sadiq; H. Hussein1, Falah; F. Karam2, Faiq (Asian Journal of Chemistry, 2014)
This study was focused on the spatial and monthly variation in the concentration of Co, Zn and Cd in surface water of Shatt Al-Hilla river. Fourteen sampling sites have been selected of pollution located on the both banks of Shatt Al-Hilla river. Samples were analyzed by flame atomic absorption spectrometry. Several physico-chemical properties of water samples were measured during period of study such as pH values, electric conductivity and temperature of water. Study was started from November 2011 and finished in October 2012. The concentrations of heavy metals under concern exhibit wide variation from site to site and from month to month. The pH values were ranged between 6.4 to 8.9, while electric conductivities were ranged between 819 to 1250 μS. The concentrations of Co and Zn were ranged 0.012 to 5.400 and 0.10 to 2.30 mg/L, respectively whereas Cd was detected in 0.007-1.550 mg/L range.